Impact of lymph node staging techniques on lymphedema and quality of life in early-stage endometrial cancer: A prospective cohort study - Anna Torrent; Joana Amengual; Angela Ruiz; Aina Serra; Laura Fuertes; Catalina Maria Sampol; Mario Ruiz; Jorge Rioja; Pilar Roca; Octavi Cordoba (Gynecologic Oncology Reports)
Background: Sentinel lymph node (SLN) biopsy is increasingly replacing complete pelvic lymphadenectomy (CL) for staging early-stage endometrial cancer (EC), but its long-term impact on patients’ quality of life (QoL) and lymphedema remains underexplored. Objective: To compare overall health perception (oHP), health-related QoL (HRQoL), and symptomatic lymphedema in patients staged with SLN versus CL. Secondary objectives included the assessment of symptomatic lymphedema and surgical complications. Methods: We conducted a prospective single-center observational study including 97 patients treated early-stage EC, with 50 undergoing SLN plus CL and 47 undergoing SLN only. Patients completed EQ-5D-3L, oHP scale (0–100), and the self-reported lower-extremity lymphedema questionnaire (LELQ) at baseline and 6-month follow-up. Multivariate analysis adjusted for confounders including surgical approach and adjuvant therapy. Results: At 6 months, the SLN group reported significantly better oHP (median 85 vs. 70; p = 0.001) and HRQoL impairment (median score 5 vs. 7; p = 0.001) than the CL group. Symptomatic lymphedema (LELQ > 5) was significantly lower in the SLN group (7.0 %) than in the CL group (34.4 %, p = 0.002). No significant differences in intra- or postoperative complications were observed. Conclusion: SLN biopsy was associated with improved QoL and lower incidence of lymphedema compared to complete lymphadenectomy. These findings support the use of SLN mapping as the preferred nodal staging technique to minimize morbidity and enhance survivorship outcomes in early-stage EC patients.